2016
DOI: 10.1007/s12088-016-0577-5
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Forest Age on Soil Fungal Community in a Northern Temperate Ecosystem

Abstract: The polymorphisms of soil fungal rDNA Internal Transcribed Spacer regions were studied in Korean pine forests of various ages (10-100-year-old trees) by means of cloned libraries, and analyzed to determine the effects of the trees' developmental stage on soil fungal community structure. The obtained Shannon diversity index (H) and richness (S) indicated that the diversity of the soil fungal community increased significantly with the development of Korean pines (P \ 0.05). In addition, cluster analysis (UPGMA) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
5
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(7 citation statements)
references
References 31 publications
2
5
0
Order By: Relevance
“…Plant growth indirectly affects the soil microbial community through soil chemical properties. This finding was consistent with those of many previous studies [ 54 , 55 ]. In addition, the Loess Plateau is in an arid and semi-arid region.…”
Section: Discussionsupporting
confidence: 94%
“…Plant growth indirectly affects the soil microbial community through soil chemical properties. This finding was consistent with those of many previous studies [ 54 , 55 ]. In addition, the Loess Plateau is in an arid and semi-arid region.…”
Section: Discussionsupporting
confidence: 94%
“…This is consistent with previous studies showing that changes in soil biodiversity in Eucalyptus plantations depend on the age of the plantation and are in parallel with the succession process of Eucalyptus trees (Chen et al, 2011;Zhang et al, 2013). Similar observation results were obtained in boreal Pinus sylvestris (Lim and Berbee, 2013) and Tsuga mertensiana (Kyaschenko et al, 2017) forests, northern temperate Quercus mongolica (He et al, 2016) and Pinus koraiensis (Zhiguang et al, 2016) forests, and Chinese subtropical Phyllostachys praecox (Li et al, 2017) forest, in which the changes in the fungal community were likely parallel with shifts in soil properties and vegetation composition caused by potential feedback on the tree stand age.…”
Section: Discussionsupporting
confidence: 92%
“…With the increased age of Eucalyptus plantations, changes in fungal community structure were apparent at both low and high taxonomic levels. Several studies have shown that the abundance of Ascomycota decreased, while that of Basidiomycota increased in forest soil across plantation age (Zhiguang et al, 2016 ; Zheng et al, 2017 ). In this study, the relative abundance of phylum Ascomycota and its orders Pleosporales, Chaetothyriales, and Eurotiales decreased, whereas that of phylum Basidiomycota and its orders Agaricales, Sebacinales, Cantharellales, and Russulales increased with the increase in the age of the Eucalyptus plantations.…”
Section: Discussionmentioning
confidence: 99%
“…Another two RS of OTU_11128 and OTU_13176 matched against uncultured Rozellomycota sp. (JQ666560 and JQ666534) with 100% identity and coverage, respectively, which were recovered from forest soil of Changbai Mountain of China (Han et al, 2016). Additionally, 59 OTUs that had less than 95% identity against sequences in the database, indicating a substantial diversity of Rozellomycota sequences that represent undescribed and diverse taxonomic groups inhabiting in the sediment of the Chinese intertidal region.…”
Section: Discussionmentioning
confidence: 99%